The Relevance of the Curriculum Early Childhood Islamic Education Study Program to Employment Needs - Mulyana, Asep; Syifauzakia, Syifauzakia; Wahyudi, Ayu Vinlandari; Shifwatussolihat, Shifwatussolihat (JURNAL PENDIDIKAN USIA DINI, 2024)
The workforce tests the skills students acquire during their studies. This study aims to analyze how the curriculum of the Early Childhood Islamic Education Study Program aligns with the competencies required in the workforce. In addition, this study evaluates the competitiveness of alumni and the level of satisfaction of the institutions that employ them. This study employs a mixed method, also known as a mixed method, along with a sequential explanatory design. Random sampling techniques selected a total of 45 alumni and 16 alumni users as samples. We collected quantitative data through surveys and obtained qualitative data through structured interviews and focus group discussions. We analyze quantitative data using descriptive statistics and interactively analyze qualitative data. The results showed that 97.78% of courses are relevant to work needs, and 98% of alumni competencies are in accordance with the demands of the workforce. However, the curriculum requires adjustments to face the challenges of the 21st century, such as technology integration, cooperative learning, application of differentiated learning, and a holistic learning approach. Additionally, the curriculum needs to adapt to current trends in early childhood Islamic education, including emotional management, smart device use, artificial intelligence, and STEAM-based learning design.